Respon Pertumbuhan Palntlet Dendrobium Sp. Pada Media Dasar Dengan Penambahan Ekstrak Buah - Dwi Kartika Risfianty; Irna Il Sanuriza; Khaerul Ikhwan; Baiq Naili Dewi Atika; Sinare Sinare; Siti Fajriah (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
Dendrobium Sp is one type of orchid plant with the most popular species both among cultivators and entrepreneurs of orchid growers. Dendrobium Sp has flowers with basic colors that have been found, namely white, purple, red, yellow, blue, brown, and a combination of these basic colors. This research was carried out by adding a supplement drink to the basic media which showed good orchid growth, using the M-150 supplement with a concentration of 25 ml added to Vacin and Went media which gave good results on rooted palntlets and number of roots. This study used a completely randomized design (CRD) with 5 treatments, the treatments were repeated 5 times so that there were 20 treatment bottles (each bottle contains one plant). Observational data were analyzed using the Analysis of Variance at the 5% level